PENGARUH PERFORMANCE AUDIT TERHADAP PENINGKATAN KINERJA PEGAWAI PADA PT PELABUHAN INDONESIA IV (PERSERO) CABANG MAKASSAR - Ibrahim Ibrahim (AkMen JURNAL ILMIAH, 2019)
This study aims to determine the effect of Performance Audit toward improving employee performance at PT. PELABUHAN INDONESIA IV (Persero) Makassar Branch. The analysis method; Data Quality Test consisting of; Validation test and reliability test. Classical Assumption Test consists of Normality Test, Multicollinearity Test, and Heterocystaticity Test. The hypothesis will be tested by using two regression models, they are (a) regression model hypothesis tested partially: Y = β0 + β1 X and (b) regression model tested simultaneously: Y = β0 + β1 X1 + β2X2 + β3X3. The results of the study show that from economic aspects, efficiency and effectiveness had a significant and positive effect toward employee performance. From the result, it can be concluded that the bigger economical aspect, efficiency, and effectiveness aspect which assessed by an auditor, then the bigger also the effect toward the employee performance.